Pd/C-Cu mediated direct and one-pot synthesis of γ-ylidene butenolides - Rambabu, Dandela; Bhavani, S.; Nalivela, Kumara Swamy; Mukherjee, Soumita; Rao, M. V. Basaveswara; Pal, Manojit (Tetrahedron letters, 2013)
10% Pd/C in combination with CuI, PPh3, and Et3N has been identified as an effective catalyst system for the coupling of (Z)-3-iodoacrylic acid with terminal alkynes in 1,4-dioxane leading to the one-pot synthesis of γ-ylidene butenolides. The methodology showed remarkable regio- and stereoselectivity as only the five-membered lactone ring products were formed with an exocyclic double bond possessing Z-geometry.
Gesehen am 07.01.2022